A comparative study of Candida albicans mean colony counts and blood group antigens in the saliva of healthy subjects - Faezeh Khozeimeh; Mehrnaz Mohammadpour; Mehdi Taghian; Vahid Naemy (Wolters Kluwer Medknow Publications, 2014)
Background: Candida albicans is the most common opportunistic fungal species in the oral cavity. Various factors associated with C. albicans infection have been evaluated so far. In some studies, the relationship between the blood group antigens and C. albicans has been discussed. The aim of this study was to assess mean C. albicans colony counts in the saliva of healthy subjects and its relationship with ABO blood groups. Materials and Methods: This cross-sectional/analytical study was performed in the Oral Medicine Department, School of Dentistry, Isfahan University of Medical Sciences. Unstimulated whole saliva samples were obtained from 300 healthy subjects, including 100 individuals with blood group O, 100 with blood group A and 100 with blood group B. The samples were cultured on Sabouraud's dextrose agar media to determine the means of C. albicans colonies. Data were analyzed by Kruskal-Wallis and Mann-Whitney statistical tests and SPSS 16. Statistical significance was defined at P < 0.05. Results: The samples included 156 males and 144 females with a mean age of 27.52 years. The mean colony counts in the saliva of individuals with blood groups O, A, and B were 26.4, 19.84, and 21.23, respectively. There were no significant differences between the three groups (P = 0.280). Conclusion: Although the mean C. albicans colony counts in individuals with blood group O were more than those with other blood groups, the differences were not statistically significant. More research studies are needed in order to prove the role of blood groups in susceptibility to candidiasis.